Profil Lipid Darah Ayam Ras Petelur yang di beri Kitosan Iradiasi - Rajali Hotlan Siregar; Diding Latipudin; Andi Mushawwir (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2020)
Research on cholesterol and triglyceride levels in blood of laying hens adminestered chitosan irradiated was carried out in August to September at the laying chicken farm in Sukarapih Village, Sukasari District, Sumedang Regency, West Java. Blood sample was analyzed at the Laboratory of Animal Physiology and Biochemistry of the Faculty of Animal Husbandry, Padjadjaran University, Jatinangor District, Sumedang Regency, West Java. This research was conducted to determine the effect of chitosan irradiation on cholesterol levels and triglyceride levels blood plasma of layer chicken. The research used an experimental method with orthogonal polynomial test. There were 50 laying hens phase layer as research object, five types of treatment, P0 = laying hens without Chitosan, P1 = laying hens with granting Chitosan 150 ppm, P2 = laying hens with granting Chitosan 200 ppm, P3 = laying hens with granting Chitosan 250 ppm, and P4 = laying hens with granting Chitosan 300 ppm. . Based on the statistic analysis result showed that administration of chitosan was significantly different (p <0.05) for cholesterol and triglyceride levels and 250 ppm was the most optimal way to reduce cholesterol and triglyceride levels.Keywords:       Laying hen, chitosan irradiation, cholesterol, triglyceride